Statin-Induced Triad of Autoimmune Myocarditis, Myositis, and Transaminitis - Muhammad Ajmal; Amitoj Singh; Saad Kubba; Michelle Hershman; Tushar Acharya (Case Reports in Cardiology)
Despite well-established cardiovascular benefits, statins have been associated with myopathic side effects ranging from myalgias to rhabdomyolysis and autoimmune necrotizing myositis. Statins have not been previously shown to cause myocarditis. Our case highlights this rare entity.